Pengaruh Jus Tomat Terhadap Penurunan Tekanan Darah Lansia Dengan Hipertensi - Hapipah Hapipah; Ulfatul Izzah; Maelina Ariyanti; Istianah Istianah (Citra Delima Scientific journal of Citra Internasional Institute, 2019)
Hypertension is degenerative disease that suffered not only by old age selves, but also it can attacks young age, as well as those that occur in the Work Area of Karang Pule Public Health Center. Tomato is one of the fruits that can decrease blood pressure in hypertension. Ingredients in tomatoes that have been known take role in decreasing of blood pressure is lycopene, bioflavonoid and potassium. The aim of thisresearch is to know the effectiveness of tomato juice toward the decrease of blood pressure in elderly with hypertension. The research design used in this research is pre-experiment design with one group pre-post test and data collection conducted using purposive sampling with 16 respondents. This research conducted for 7 days and the respondent measured his blood pressure 10 minutes before tomato juice consumption, and 30 minutes after consumption of tomato juice. The result of the analysis of Wilcoxon of blood pressure decrease with statistically significant result p = 0.000 (p <0,05), meaning that the result of analysis showed that the decrease of systole and diastole blood pressure after tomato juice. Based on the results of this research, It can concluded that drinking tomato juice daily can decrease of blood pressure significantly in patients with hypertension. Key words: Hypertension, Tomato Juice, Elderly